The Effect of Ethical Anxiety, Ethical Risk Perception, and Ethical Awareness on Students' Academic Performance Through the Use of Generative AI - Putri Natami Nainggolan; Ratna Candra Sari (International Journal of Economics, Management and Accounting, 2026)
This study analyzes the influence of Ethical Anxiety, Ethical Risk Perception, and Ethical Awareness on students’ Academic Performance, with the use of Generative AI as a mediating variable. The method employed is quantitative, using the SEM-PLS approach with 41 questionnaire items. The results indicate that the instruments are valid and reliable, with R-squared values of 0.727 for Generative AI Usage and 0.705 for Students’ Academic Performance. Surprisingly, Ethical Anxiety and Ethical Risk Perception have a significant positive effect on Generative AI Usage, which partially mediates their impact on Academic Performance. However, mediation does not occur in the relationship between Ethical Awareness and Academic Performance. These findings suggest that ethical factors play an important role, but their influence on AI usage and its impact on academic outcomes is not uniform within the academic environment.